Obstructive jaundice in autoimmune pancreatitis can be safely treated with corticosteroids alone without biliary stenting - Bi, Yan; Hart, Phil A.; Law, Ryan; Clain, Jonathan E.; Farnell, Michael B.; Gleeson, Ferga C.; Kendrick, Michael L.; Levy, Mike J.; Pearson, Randall K.; Petersen, Bret T.; Pisney, Lisa D.; Smyrk, Thomas C.; et al. (Pancreatology : official journal of the International Association of Pancreatology (IAP) ... [et al.], 2016)
Autoimmune pancreatitis (AIP) responds dramatically to corticosteroids treatment. We reviewed our experience to determine the safety and effectiveness of treating obstructive jaundice in definitive AIP with corticosteroids alone without biliary stenting. From our AIP database, we retrospectively identified type 1 AIP subjects whose jaundice was treated with corticosteroids alone without biliary stenting. Their medical records were reviewed and clinical data were evaluated to determine the outcomes. Fifteen AIP subjects (87% male, mean age 68.4 years) were treated with corticosteroids at initial presentation (n = 8), first (n = 5) or subsequent (n = 2) relapse. Mean values (upper limit of normal, ULN) of liver tests prior to corticosteroids were aspartate aminotransferase (AST) 203.5u/l (4 × ULN), alanine aminotransferase (ALT) 325.8u/l (6 × ULN), alkaline phosphatase (ALP) 567.4u/l (5 × ULN), and total bilirubin (TB) 5.9 mg/dl (5.9 × ULN). At first follow-up (mean 4 days) the decrease was 54.9% for AST, 51.6% for ALT, 33% for ALP and 47.2% for TB (all p < 0.05). After 15–45 days, all patients had normal AST, 3/15 had ALT > 1.5 × ULN, 1/15 had ALP > 1.5 × ULN, 1/15 had TB > 1.5 × ULN. No patient required biliary stent placement, or developed cholangitis or other infectious complications during steroid treatment. Under the supervision of an experienced pancreatologist and with close monitoring of patients, obstructive jaundice secondary to definitive AIP can be safely and effectively managed with corticosteroids alone, without the need for biliary stenting.